Force Analysis of Material Movement in a Horizontal Mixer of a Hydrolytic Chamber: a Case Study of Soybean Meal Processing - M. G. Zagoruiko; M. E. Belyshkina; I. A. Bashmakov; A. M. Maradudin (Сельскохозяйственные машины и технологии, 2025)
The paper addresses the increasing demand for plant-based protein in the compound feed industry. It emphasizes the role of grain legumes; particularly soy; one of the most protein-rich crops; as a primary feed protein source. Analytical studies have identified key strategies for developing a universal compound feed production line that integrates high-protein ingredients derived from soybean meal. To enhance protein digestibility and biological value; extruded soybean meal undergoes enzymatic hydrolysis in a continuous horizontal mixer. Additionally; the paper describes material movement within a hydrolytic chamber equipped with a screw-driven working unit. (Research purpose) The primary objective of the study is to conduct a force analysis of material movement in a horizontal screw mixer to determine the optimal structural and operational parameters of the hydrolytic chamber. (Materials and methods) The analysis focuses on the system of forces acting on a material particle resting on the helical surface of a horizontal screw and pressed against the inner wall of the casing. (Results and discussion) By projecting all active and assumed inertial forces acting on a material particle; a system of equations was derived. The study found that the power required to drive the screw shaft depends on multiple factors; including the condition of the screw and casing surfaces; particle mass; screw geometry; polar coordinates defining the particle’s position within the screw; and the kinematic parameters of its rotational motion. (Conclusions) The developed mathematical model of material movement; which accounts for the physical and mechanical properties of the material and the geometry of its flow; facilitates the selection of optimal structural and operational parameters for the mixer. This ensures efficient material transport during the design process.